Practices of the Qadiriyah Wa Naqsabandiyah Tariqa and Its Functions in Community Life in Jereng Hamlet Gugut Rambipuji Village – Jember - Rikiyanto, Ahmad; Asror, Ahidul; Faizin, Khoirul (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The practice of the Qadiriyah Wa Naqsabandiyah Tariqa has become an integral part of people's lives in various regions, especially in the Islamic world. This study aims to gain a deeper understanding of this spiritual practice and its impact on people's lives. The research method used is qualitative research, using in-depth interviews and participant observation to collect data. The results of the study indicate that the practice of the Qadiriyah Wa Naqsabandiyah Tariqa has a significant influence on people's lives. In a spiritual context, these practices provide a forum for self-development, introspection, and the search for the meaning of life. People who engage in these practices often report an increase in spiritual satisfaction and personal happiness. In addition, these practices also have important social impacts. They promote values ​​such as generosity, loyalty, and tolerance between individuals. This helps strengthen social relations in society and encourages cooperation and solidarity among its members. However, there are also challenges and controversies associated with the practice of the Qadiriyah Wa Naqsabandiyah Tariqa. For example, some critics worry that these practices can become a tool for oppression or social control, especially in contexts where religious authorities have strong influence. This study concludes that the practice of the Qadiriyah Wa Naqsabandiyah Tariqa has a complex and diverse impact on people's lives. Although there are pros and cons, a deeper understanding of these practices can help people maximize their benefits while minimizing their risks and negative impacts.